Sustainable food production in Sub-Saharan Africa : IITA's contributions - Russell, Nathan C.; International Institute of Tropical Agriculture (Ibadan, Nigeria : International Institute of Tropical Agriculture, 1992)
The publication commemorates the 25th anniversary of IITA's founding. It is the institute's contributions to sustaining food production in sub-Saharan Africa. With the amount of attention being given to the concept of sustainable agriculture, it made sense to present a fairly detailed account of the institute's research that would demonstrate its relevance to this issue, which now guides the planning and action of all CGIAR centers and many other organizations involved in agricultural development. Secondly, sustainability has occupied a central place in the research mission that has guided IITA's work for the last 25 years.
"Text, Nathan Russell, with various authors indicated in each chapter"--T.p. verso.
Includes bibliographical references.
rpm 20/09/16
Loans
Keywords: Food crops; Sustainable agriculture; Tropical agriculture; Africa, Sub-Saharan.